Genetic analyses for alternative reproductive traits in Nellore cattle under a Bayesian framework - Ramos, Pedro Vital Brasil (2019)
Reproductive traits are determinant for the profitability of beef cattle. Therefore, several reproductive traits are used by Brazilian breeding programs to evaluate fertility, sexual precocity and cows” longevity. Although it has been less studied, days to calving (DC) 1s a relevant alternative trait related to female”s fertility. However, it tends to present asymmetric distribution (such as Exponential) because 1t represents time to an event occurrence, 1.€., calving. In addition, some females may not present records for DC due to late calving, thus characterizing censored data. Among other important reproductive traits, currently the stayability stands out given its economic importance, since 1t 1s closely related to fertility and cow's longevity. However, stayability 1s belatedly measured (conventionally at 76 months) and enables reproductive failures in the considered evaluation period. Facing these features, the genetic improvement of females" reproductive traits 1s a wide challenge to be overcome in animal breeding. In this context, the inclusion of genomic information under a single-step (ssGBLUP) approach 1s a promising method to increase the prediction accuracy for these traits. Therefore, the following aims were exploited here: 1) to propose and evaluate the Exponential censored Bayesian model for genetic evaluation of DC in Nellore cattle taking into account the predictive ability and goodness-of-fit; 2) to perform comparison analysis (prediction accuracy) between traditional BLUP and ssGBLUP methods. 3) to propose and investigate new traits related to the cow's longevity and fertihty (stayability42, stayability53, stayability64 and consecutive rebreeding ability - CRA), as well as to evaluate their genetic associations with the conventional stayability definition (stayability63) and other productive traits. The proposed Exponential model was not indicated for genetic evaluations of DC; on the other hand, other investigated censored models can be recommended instead the conventional Gaussian model. The ssGBLUP seems to be an advantageous alternative to improve the prediction accuracy of stayabihity. In summary, stayability42 can be a feasible selection criterion for reproductive efficiency in young females; whereas the staybility53 can be additionally indicated for female”s longevity, since 1t 1s closely related to cow's fertihty and can be measured earlier than the conventional stayability63. Finally, the proposed CRA has shown to be a promising alternative for fertility selection in Nellore females.